2020
DOI: 10.2478/aussoc-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Depression in Medical Assistants in State-Owned Healthcare Institutions in Romania

Abstract: Similarly to other countries in the Eastern European Region, the situation of medical assistants in Romania is fairly difficult. Due to the lack of personnel, health professionals are typically overwhelmed with work. The Quality of Life Research Centre at Sapientia Hungarian University of Transylvania conducted a non-representative survey among medical assistants in Romanian state-owned healthcare institutions. The sample size is 312 Romanian and Hungarian speaking nurses from six counties. The present study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The authors concluded that nursing assistants endorsing more supportive work environments, as a proxy for teamwork, may be more likely to adjust to workforce factor changes ( Noelker et al, 2006 ). Similarly, Sántha et al (2020) found that protection from both burnout and depression risk among medical assistants increased with the number of general supportive relationships. More specifically, another study found higher organizational respect and less emotional exhaustion post-implementation of a policy and practice change that promoted improved unit-based culture (defined as greater respect for peers, increased involvement of nursing assistants in team decision making, and increased valuation of cultural perspectives) ( Ramarajan et al, 2008 ).…”
Section: Resultsmentioning
confidence: 89%
“…The authors concluded that nursing assistants endorsing more supportive work environments, as a proxy for teamwork, may be more likely to adjust to workforce factor changes ( Noelker et al, 2006 ). Similarly, Sántha et al (2020) found that protection from both burnout and depression risk among medical assistants increased with the number of general supportive relationships. More specifically, another study found higher organizational respect and less emotional exhaustion post-implementation of a policy and practice change that promoted improved unit-based culture (defined as greater respect for peers, increased involvement of nursing assistants in team decision making, and increased valuation of cultural perspectives) ( Ramarajan et al, 2008 ).…”
Section: Resultsmentioning
confidence: 89%